Gong ensemble in SMK Lohan and its implications to music education / Nor Soleha Laila Nasimin - Nasimin, Nor Soleha Laila (Faculty of Music, 2017)
This study is about the gong ensemble in SMK Lohan and how the group is managed as well as how its members perceived their participation. The implications to music education is discussed at the end of the project. This study was conducted using qualitative research method for the purpose of looking at the teaching of the gong ensemble at SMK Lohan. The sample for this project consisted of the teachers and students involved with the gong ensemble at SMK Lohan which is located in Kampung Lohan Ulu, Sabah. Information gathered throughout this project was analysed to see the process of how an ensemble group is formed and maintained. The perspectives of both teachers and students addresses the issues arising from having a traditional music ensemble in a secondary school and the challenges faced by the teachers responsible for them.